Online trade marketing techniques through giveaway as one of the guise of fraud - IIdha Pratiwi Dyah Sinta Dewi; Pujiyono Pujiyono (Lembaga Penelitian dan Pengabdian Masyarakat, 2020)
Technological development also affects the economy. Nowadays commercial activities by using the internet are different from the conventional. Those who are parties to internet commerce base their transactions on trust. To build trust in customers, online merchants use marketing techniques named endorse service. Seller currently makes giveaway events on these endorser accounts. However, the gift is often not fulfilled by online merchants so that giveaway is just a guise of online fraud. The author emphasizes the relation of fraud caused by giveaway with the building of public trust through the endorsers. This crime is rarely revealed because the victims didn’t want to report. This research is a normative study using a statutory approach, data collection through library research, and analyzed using descriptive-analytical techniques. From this study, the result is an understanding that the relations between endorsers and fraudulent activities carried out by digital economics actors is by creating trust in the community, giveaway exists without further investigation of prizes. Fraud is seen as a causal subjective relations where there is an act of influencing the will of others created by endorsers so that person gives something to the seller.